Mixed Methods in Educational Large-Scale Studies: Integrating Qualitative Perspectives into Secondary Data Analysis - Jana Costa (Education Sciences)
This article highlights the integration of qualitative perspectives into the traditionally quantitative domain of large-scale studies and explores how mixed methods can overcome the limitations of predefined datasets. Different purposes for integrating qualitative perspectives before, during, and after LSAs are presented. Two examples are used to illustrate the potential and challenges of re-analyzing existing data from a qualitative perspective. Therefore, this article argues that the integration of qualitative perspectives can provide new empirical insights, allowing researchers to explore new patterns, address research gaps, and reframe theoretical foundations. In this way, mixed methods can enhance the scope of LSA data analysis, making it more adaptable to complex educational research questions and enriching the overall research process.